Grafting organic n-semiconductors to surfaces: (perfluoro-p-terphenyl-4-yl)alkanethiols - Schüpbach, Björn; Bolte, Michael; Zharnikov, Michael; Terfort, Andreas (European journal of organic chemistry, 2010)
Perfluoroterphenyl, an organic n-semiconductor, has been derivatized by short ω-mercaptoalkyl chains to permit the formation of self-assembled monolayers on semiconductor and coinage metal substrates. Because the perfluoroaryl rings are prone to nucleophilic attack, strategies for the introduction of the side chains had to be developed that avoid the use of any nucleophiles. Keeping this in mind, the respective derivatives with one, two, and three methylene groups in the alkyl linker could be obtained in good yields. The crystal structure of one of the intermediates, (perfluoroterphenyl-4-yl)methanol, exhibits a parallel arrangement of the molecules as well as a helical structure of the perfluoroterphenyl part, which is in contrast to the structure found for most nonfluorinated terphenyl derivatives. Using Au(111) as a test substrate, it could be demonstrated that all three thiols form dense monolayers with a pronounced odd-even effect governed by the parity of the number of methylene groups in the alkyl chain.